Review for Citrus hystrix DC. - Ut, Le Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
Herbal medicines have played a critical role in the treatment and prevention of some diseases. Among a diversity of natural medicinal sources, Citrus hystrix DC. is an outstanding plant broadly distributed in tropical regions. Citrus hystrix DC. has many biological activities, and it has been used in traditional medicine for treating various illnesses, particularly cold pain and stomach disorder. This review article focuses to enhance and prepare a comprehensive review on phytochemical and pharmacological studies of Citrus hystrix DC., and aims to lay the foundation for further study on the extraction enhancement of these biomolecules and more useful formulations. Based on published scientific data, these plants may suggest a gigantic biological potential of an abundant source of chemical constituents and a variety of bioactivities contributing to therapeutic values.